Intravenous Anesthesia in a Rare Pediatric Patient with Poland Syndrome: Case Report - Wan Novriza Wijaya; Dino Irawan; Novita Anggraeni (Green Publisher Indonesia, 2026)
Poland syndrome (PS) is a very rare congenital anomaly characterized by hypoplasia or aplasia of the pectoral muscles and mammary hypoplasia and is associated with anomalies in the ipsilateral region of the body. Poland syndrome can increase the risk of developing intraoperative malignant hyperthermia; hence, special consideration is needed in the management of anesthesia in these patients. We report herein the management of general anesthesia for syndactyly release surgery in a child with Poland syndrome. A 1-year- and 11-month-old boy with Poland syndrome was scheduled to undergo manus dextra interphalangeal syndactyly release surgery under total intravenous general anesthesia using midazolam (0.1 mg/kg body weight), fentanyl (2 mcg/kg), and atracurium (0.5 mg/kg body weight) as induction agents, with maintenance using midazolam (0.3 mg/kg/h). Anesthesia can be performed at this age to prevent contractures and deformities and to avoid functional abnormalities. The anesthesia lasted 120 min with intraoperatively stable hemodynamics. After the operation, the patient was treated in a regular ward and discharged after 2 days of treatment. The use of total intravenous anesthesia with midazolam in children with Poland syndrome for the surgical release of manus dextra interphalangeal syndactyly is a good option and is also clinically beneficial.